Risk Management in Petrochemical Companies: Sankyu Company as Case Study - Alharbi, Ziyad Salem Awad (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
Numerous risks associated with petrochemical projects can lead to cost overruns and negatively impact the quality of petrochemical products. These problems result from a failure to implement a plan to manage risks related to the operation and maintenance of petrochemical equipment and machinery. Therefore, this study aims to examine the risk mitigation strategies represented by risk retention, risk control, risk prevention, and risk transfer related to improving the financial aspects of petrochemical projects. To achieve the research objectives, the study relied on the quantitative approach by using a questionnaire that included the definition of all potential risks related to operational, human, environmental, and maintenance risks. The questionnaire also included an extensive study of risk mitigation strategies. The organization distributed the questionnaire to 268 Sankyu Company employees who operate and maintain petrochemical equipment. The study sample reached 159 respondents. The SPSS statistical analysis program calculated averages and standard deviations after collecting the data. The study found that the potential risks assessed using the risk index have a significant impact on petrochemical projects. The study also provided a comprehensive guide that includes risk mitigation strategies in petrochemical projects. The study has proven effective in improving the financial aspects of petrochemical projects.